(untitled) - Garsten, Christina (New York, 2004)
Globalization of trade and organizational change increase the impact of markets in people's lives. But in what ways do markets matter? This book is about how financial analysts, marketing people, corporate leaders and other actors in Western market economies perceive, model, and use markets. It provides an ethnographic window into the cultural processes of contemporary markets; how people employ the market to solve problems, create capital, gain political ends, challenge economic processes, and delineate moral values and responsibilities.
Keywords: Economic anthropology,Globalization,Capitalism,Markets; Economic aspects